Views of The Assembly and “Shighat” On The Contract and Their Relevance to Contemporary Economic Dynamics - Nizar, Firman; Triana, Nita (Al-Amwal : Journal of Islamic Economic Law, 2024)
Purpose  –  The problem in Islam is that economic activity is closely related to contracts. Ijab and Qabul are the essence of the contract, namely the will of the offeror and the will of the recipient of the consent.Method –  This relates to research that explains the concepts of assembly and sighat views in contracts and their relevance to contemporary economic dynamics.Result – The results of this research show that the majlis and sighat in the contract have several meanings according to the views of four madzhab scholars, some of whom argue that ittihad al-majlis does not have to be united in one place, but rather the ijab and kabul are in one place, meaning the person who will do the ijab and the kabul does not have to be in one place and neither do the witnesses.